Clinical Exome Sequencing as a Novel Tool for Diagnosing Loeys-Dietz Syndrome Type 3. Issue 6 (December 2015) - Blinc, A.; Maver, A.; Rudolf, G.; Tasič, J.; Pretnar Oblak, J.; Berden, P.; Peterlin, B.
Abstract : Objective/Background: In rare genetic vascular syndromes the diagnosis may not be apparent from the phenotype, but might be important for proper management. Methods: A previously healthy woman without dysmorphic features presented with pregnancy associated vascular dissections and aneurysms. Next generation clinical exome sequencing was performed. Results: The differential diagnosis of spontaneous arterial dissection is outlined. The patient's diagnosis became evident after clinical exome sequencing detected a novel missense mutation in the evolutionary conserved region of SMAD3, confirming the diagnosis of Loeys-Dietz syndrome (LDS) type 3. A brief overview of the various types of LDS and their management is presented. Conclusion: Clinical exome sequencing proved useful in diagnosing LDS type 3 where detailed vascular surveillance and timely intervention with a low threshold is recommended.